Towards a global higher‐frequency sea level dataset. (24th February 2017) - Woodworth, P. L.; Hunter, J. R.; Marcos, M.; Caldwell, P.; Menéndez, M.; Haigh, I.
Abstract : This paper describes the assembly of an updated quasi‐global dataset of higher‐frequency sea level information obtained from tide gauges operated by many agencies around the world. We believe that the construction of such a dataset is fundamental to scientific research in sea level variability and also to practical aspects of coastal engineering. A first version of the dataset was used in approximately a dozen published studies, and this second version is about twice the size, containing longer and more geographically representative sea level records. The dataset has acquired a digital object identifier and may be obtained from several sources. The paper mentions some of the merits of and deficiencies with the present version and takes a forward look at how the dataset may be updated in the future.